INTEGRASI TEKNOLOGI CERDAS DALAM TATA RUANG KANTOR LEMBAGA PENDIDIKAN ISLAM - M. Yusuf (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The integration of smart technology in the office space of Islamic educational institutions has become a major focus in enhancing efficiency and service quality. This article aims to explore the benefits and implications of such integration. The background of this research lies in the need for efficient and user-friendly workspace design in the context of quality Islamic education. The research method employed in this study is a literature review, analyzing scholarly journals, books, and relevant articles as data sources. The findings indicate that the integration of smart technology in office space can improve administrative efficiency, staff productivity, and student learning experiences. Examples of smart technology that can be integrated include the Internet of Things (IoT), smart security systems, and room management solutions. In the context of Islamic educational institutions, this integration holds the potential to enhance effective educational management and fulfillment of educational needs. Thus, the integration of smart technology in the office space of Islamic educational institutions has significant and vital implications for the advancement of Islamic education.